Soccer: Aceleration & deceleration - Tang, R. (Kitman Labs 2017 European Summit, 2017)
Earlier this year Kitman Labs' hosted our first, annual Performance Summit in the UK, London. Amongst the many talented presenters was Performance Scientist, Remy Tang, who shared his research on accelerations and decelerations in professional football. His research highlights the importance in considering how accelerations and decelerations contribute to player fatigue and the overall physiological cost on the team, and how this may impact performance throughout the season. More pertinently by identifying higher intensity accelerations and decelerations, backroom staff will develop a greater awareness and control of the overall external and internal demands for players.